Prawo dostępu do informacji publicznej w ramach prawa Ukrainy: treść, gwarancje oraz problemy realizacji - Âvors′ ka, Oleksandra (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
This article analyzes current Ukrainian legislation that regulates content and guarantees of the subjective right to access to public information and its implementation.The content of the subjective right to information includes following elements: the right to collect, the right to remain and the right to use and distribute information. However, the content of the right to information cannot wane or to be seen solely in terms of private law regulation. In order to ensure the proper implementation of this right, it is important to legislate the respective responsibilities of authorized entities including government entities to provide a person with objective information.In Ukraine, there is an existing appropriate regulatory framework that ensures mechanisms for realization and protection of the right of access to public information and information that is of public interest. First of all, they are Ukrainian laws «On access to public information» that was signed on January 13, 2011, and «On access to archives of the repressive totalitarian communist regime during 1917–1991 years» signed on April 9, 2015. As well as national regulation that is examined in the light of the provisions of the European Convention on Human Rights and the Council of Europe Convention on Access to Official Documents.Examined problems of legal regulation associated with the promulgation of public information and making it available on request. Because of that fact that information is public, no one can set access restrictions, except as required by law.Such information must not be regarded as confidential, secret or information with limited access.The mechanism of implementation the right of access to public information is complicated by unclearness vagueness of some concepts for the lack of certainty of criteria as for example information that is of public interest, substantial harm from disclosure, etc. Grounded proposals for improving the legal regulation of social relations in this sphere
Keywords: dostęp do informacji publicznych; informacje poufne; informacje służbowe; ograniczenie dostępu do informacji publicznych